2007
DOI: 10.1061/(asce)0733-9429(2007)133:3(255)
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Stratification and Shoreline Erosion on Reservoir Sedimentation Patterns

Abstract: Sedimentation in the main pool of a deep ͑maximum depth: 50 m͒, 227 km 2 hydropower reservoir was modeled using a three-dimensional numerical model of hydrodynamics and sedimentation for different wind, inflow, and outflow conditions. Short-term velocity measurements made in the reservoir were used to validate some aspects of the hydrodynamic model. The effects of thermal stratification on sedimentation patterns were investigated, since the reservoir is periodically strongly stratified. Stratification alters v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 20 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…Erosion is caused by wave impact and surface runoff that are both spatially and temporally variable. Research is needed to describe the intensity of wave erosion during the low water level of 145 m and the high one of 175 m. Empirical relationships between driving forces of wave erosion such as fetch and wind velocity (Elçi et al, 2007) and the amount of eroded materials at each elevation should be created to quantify the degree of wave erosion. It should be useful to identify or create a quantitative index (or several indices) to represent independent variable(s) in these quantitative relationships.…”
Section: Geomorphological Aspectsmentioning
confidence: 99%
“…Erosion is caused by wave impact and surface runoff that are both spatially and temporally variable. Research is needed to describe the intensity of wave erosion during the low water level of 145 m and the high one of 175 m. Empirical relationships between driving forces of wave erosion such as fetch and wind velocity (Elçi et al, 2007) and the amount of eroded materials at each elevation should be created to quantify the degree of wave erosion. It should be useful to identify or create a quantitative index (or several indices) to represent independent variable(s) in these quantitative relationships.…”
Section: Geomorphological Aspectsmentioning
confidence: 99%
“…However, in cases of strong stratification a density current is unlikely. In this case, grains can be transported by currents within the water body [ Elçi et al , 2007; Marti and Imberger , 2008]. In laboratory experiments and with the help of a linear model, Stevens and Imberger [1996] showed that in stratified waters under wind stress, a return flow in upwind direction can establish in the thermocline, and the flow velocities in this return current can be of the same order as the friction velocity at the lake surface.…”
Section: Sediment Data and Analysismentioning
confidence: 99%
“…The model can also simulate wetting and drying conditions of the grid cells. The model has been applied to several water systems (Shen and Kuo 1999, Tetra Tech Inc. 1999, Jin et al 2000, 2002, Elçi et al 2007, Ç alışkan and Elçi 2009. A detailed description of EFDC is provided in Hamrick (1996).…”
Section: Modeling Of Sediment Depositionmentioning
confidence: 99%
“…Reservoir sedimentation has been widely studied in the past, often focusing on the description and investigation of the mechanism that transports sediments into the reservoir (Guy et al 1966, Soni 1981, Blumberg and Mellor 1987, Falconer et al 1991, Hotchkiss and Parker 1991, Blumberg et al 1999, Jin et al 2000, Yang et al 2000, Rueda and Schladow 2003, Elçi et al 2007. Deposition rates were of primary interest in many studies and were modeled numerically (Jin et al 2000, Rueda and Schladow 2003, Elci et al 2007 or measured via surveying (Snyder et al 2006, Pratson et al 2008.…”
mentioning
confidence: 99%